Reports on the prevalence of pneumo - enteritis among sheep in Ile- Ife, Nigeria (2012)
Data were collected on the prevalence of pneumo-enteritis among 895 sheep reared ori the semi-intensive system at Obafemi Awolowo University Teaching and Research (OAUTR) farm, lle-Ife and 317 sheep brought from the free range for sale at Ile-lfe Sheep and Goat [ISG] market between the periods of December 1985 to October 1993 and November to October 1993 respectively. At OAUTR farm, 39.51% of the sheep were affected with pneumo-enteritis; 78.13% of the treated sheep [32 in number) recovered while 6.26% mortality was obtained. At ISG market 33.10% of the sheep were affected. The disease was more prevalent during the dry seasons (November to March) at OAUTR farm (9.96%) and ISG market (69.33%) than what obtained during the rainy season (April to October) at the two locations (8.08% and 21.90% respectively). The incidence of the disease was higher among sheep at ISG market than those at OAUTR farm. Bacteriological examination of nasal swabs from infected sheep revealed the presence of Pasteurella haemolytica, Pasteurella multocidci, Streptococci spp. and Coccobacillia bacteria. Prompt treatment of infected sheep elicited recovery.